Antioxidant content and activity of selected African leafy green vegetables in the gastrointestinal tract (GIT) : determination using simulated GIT digestion - Bester, Marthan Nieuwoudt (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.